2021
DOI: 10.3389/fcimb.2021.650407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infant Formula Supplemented With Prebiotics and OPO on Infancy Fecal Microbiota: A Pilot Randomized Clinical Trial

Abstract: Several lines of evidence suggest that the intestinal microbiota plays crucial roles in infant development, and that it is highly influenced by extrinsic and intrinsic factors. Prebiotic-containing infant formula may increase gastrointestinal tolerance and improve commensal microbiota composition. However, it remains unknown whether supplementation of milk-formulas with prebiotics and 1,3-olein-2-palmitin (OPO) can achieve feeding outcomes similar to those of breastfeeding. In the present study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
6
13
0
Order By: Relevance
“…Previous reports have shown that infant formula supplemented with OPO shapes the structure and function of the gut microbiota (Yao et al, 2014;Zhu et al, 2021). The overall diversity and composition of the gut microbiota are more similar to that of breast milk.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous reports have shown that infant formula supplemented with OPO shapes the structure and function of the gut microbiota (Yao et al, 2014;Zhu et al, 2021). The overall diversity and composition of the gut microbiota are more similar to that of breast milk.…”
Section: Introductionmentioning
confidence: 90%
“…At the same time, OPO improves the stool state, reduces stool hardness, and relieves constipation (Meneses et al, 2008). In addition, several studies have shown that OPO improves the balance of intestinal microbes in infants, activates immune cells, and improves immunity (Lu et al, 2013;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…infantis, which is tailored towards the metabolism of human milk oligosaccharides (HMO) [ 30 , 31 ]. For infants fed on formula milk, infant formulae are commonly fortified with prebiotics so as to confer similar beneficial components as those found in breastmilk [ 32 , 33 , 34 ]. Prebiotics are “substrates that are selectively utilized by host microorganisms conferring health benefits to the host” [ 35 ].…”
Section: The Human Gut Microbiome In Health and Diseasementioning
confidence: 99%
“…These prebiotics have been shown to beneficially alter the gut microbiota of infants by selectively enhancing the growth of Bifidobacterium and lowering the abundance of Enterococcus and Escherichia coli [ 36 , 37 ]. However, GOS and FOS are structurally different from HMO [ 38 ] and so do not entirely replicate the beneficial effects of HMOs on the infant gut microbiota, for example, on a species level [ 34 , 39 , 40 ]. Nevertheless, it has been noted that an infant diet supported by prebiotic formula results in fewer infections than a placebo formula does, and so non-HMO prebiotics appear to have a positive impact in infants [ 41 ].…”
Section: The Human Gut Microbiome In Health and Diseasementioning
confidence: 99%
“…In recent years, the infant formulas have been enriched with bioactive ingredients (e.g., probiotics, prebiotics, polyunsaturated fatty acids, synthetically produced HMOs) to mimic the composition of the human milk. However, the beneficial effects of this supplementation on both, fecal microbiome, and metabolome are discussed (65,(78)(79)(80).…”
Section: Human Milk Vs Formula Feedingmentioning
confidence: 99%